Penegakan Hukum Pidana dalam Upaya Merestorasi Dampak Ekologis Penambangan Nikel di Raja Ampat - Teti Ratnasari; Hendri Darma Putra (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The background of this problem arises from the importance of Raja Ampat as a world conservation area with abundant marine biodiversity, but faces various ecological threats due to human activities such as mining and environmental pollution. The research method used is a statutory approach to analyze national andinternational legal arrangements related to environmental protection and conservation in Raja Ampat, followed by a conceptual approach to understand the principles of sustainability and ecological crime. The case study approach to nickel mining activities in the region provides a real picture of implementation and law enforcement challenges, including the effectiveness of supervision and prosecution of environmental law violations. Data were obtained from official documents, interviews, and field observations to ensure the accuracy and validity of the analysis. Conclusions show that firm and consistent criminal law enforcement, supported by cross-agency collaboration and the participation of indigenous communities, is critical to reducing ecological damage and ensuring the sustainability of Raja Ampat's marine ecosystems in a sustainable and equitable manner.